2019
DOI: 10.3389/fimmu.2019.02204
|View full text |Cite
|
Sign up to set email alerts
|

The Era of Thromboinflammation: Platelets Are Dynamic Sensors and Effector Cells During Infectious Diseases

Abstract: Platelets are anucleate cells produced by megakaryocytes. In recent years, a robust body of literature supports the evolving role of platelets as key sentinel and effector cells in infectious diseases, especially critical in bridging hemostatic, inflammatory, and immune continuums. Upon intravascular pathogen invasion, platelets can directly sense viral, parasitic, and bacterial infections through pattern recognition receptors and integrin receptors or pathogen: immunoglobulin complexes through Fc and compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
208
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(219 citation statements)
references
References 170 publications
(234 reference statements)
4
208
0
7
Order By: Relevance
“…Conversely, our multivariate analysis showed that, as the PDW values increased, the probability of death decreased. Thus, our data suggest the role of platelets as host defense effectors in agreement with these studies [38][39][40][41][42] .…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, our multivariate analysis showed that, as the PDW values increased, the probability of death decreased. Thus, our data suggest the role of platelets as host defense effectors in agreement with these studies [38][39][40][41][42] .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to agonist-activation, the binding of pathogens can trigger granule cargo release [31] and liberation of "platelet microbial" proteins and peptides, including platelet factor (PF)-4, regulated on activation, normal T cell expressed and secreted (RANTES), and fibrinopeptide B. Platelets may also play an important role in the clearance of viral pathogens. Platelet interactions with leukocytes trigger recruitment and tissue infiltration necessary for pathogen clearance (reviewed in Guo [32]. In critically ill patients, The available clinical and pathological evidence, coupled with strong and mature data that supports a relationship between CFRNA, polyphosphate and factor XI activation, raises a logical scientific premise that requires investigation.…”
Section: Platelets In Covid-19-associated Thrombosismentioning
confidence: 99%
“…Finally, during an E. coli infection, thromboinflammation is upregulated by simultaneous activation of FcγRIIA receptors and the αIIbβ3 integrin on platelets [ 25 ]. Bacterial killing of E. coli by platelets requires both FcγRIIA and platelet factor 4 (PF4) in order for destruction to occur [ 26 ]. Although the αIIbβ3 integrin is not directly involved in immune response against E. coli , it is a necessary component for the activation of platelet FcγRIIA and can lead to an upregulation of thromboinflammation.…”
Section: Adhesion Receptors In Platelets Are Crucial For Platelet mentioning
confidence: 99%
“…Neutrophils in PNCs display a greater level of activation than those uncoupled from platelets, expressing more superoxide and phagocytosing more bacteria than their counterparts [ 31 ]. In fact, terms like “thromboinflammation” and “immunohemostasis” have gained traction in recent years in order to properly describe the interactive role of PNC’s in the immune response [ 26 ]. Upon activation via a variety of infection or inflammation mechanisms, platelets can change expression of their surface receptors to attach to other platelets, leukocytes, or extracellular pathogens, forming a complex that can help sequester and eliminate the pathogen [ 26 ].…”
Section: Adhesion Receptors In Platelets Are Crucial For Platelet mentioning
confidence: 99%